Ownership of small livestock species, but not aggregate livestock, is associated with an increased risk of anemia among children in Ethiopia: A propensity score matching analysis - Zerfu, Taddese Alemu; Abera, A.; Duncan, Alan J.; Baltenweck, Isabelle; McNeill, Geraldine (Wiley, 2023)
Consumption of animal source foods, through livestock production, improves children's growth and micronutrient status. However, research on the relationship between livestock ownership and childhood anemia has produced conflicting results. The current study used robust analytical approaches to examine the effect of household livestock ownership on children's anemia using the most recent secondary data from the national demographic and health survey. We followed a 1:1 closest neighborhood propensity score matching analysis. A propensity score was generated using the binary logistic regression model to compute the probability of owning livestock. From a total of 18,008 households enrolled in the latest Ethiopian Demographic and Health Survey (EDHS 2016), data of 721 index children aged 6–59 months from households owning livestock were matched with a comparable number (721) of children from households without livestock. The paired and independent t-test, matched relative risk (RR), and standardized mean differences were used to compare the distributions of hemoglobin concentration and anemia risks between treatment and control groups. Anemia was found in more than half (54.1% and 58.8%) of children aged 6–59 months from livestock-owning and nonowning families, respectively (p > .05). Aggregate ownership of livestock was not associated with hemoglobin concentration or anemia status (RR = 0.95, 95% confidence interval [95% CI] [0.87–1.04]). Species-wise, poultry was associated with a lower (RR = 0.88, 95% CI [0.84–0.95]) anemia risk, while ownership of goat/sheep was associated with higher (RR = 1.10, 95% CI [1.03–1.17]) risk. In conclusion, ownership of small livestock species (sheep/goats and poultry), but not aggregate livestock ownership, was associated with the risk of anemia among children in Ethiopia. Therefore, agriculture-sensitive nutrition, with a One Health lens approach, is recommended to mitigate the high burden of anemia among children in Ethiopia. In the future, a well-controlled interventional study with more extended periods may be required to fully understand the effects of livestock production and highlight the differences seen across livestock species.